Impact of the Implementation of Green Human Resources Management: A Study of Systematic Literature - Lina Saptaria; Budi Eko Soetjipto; Cipto Wardoyo (Yayasan Ilomata, 2022)
The impact of implementing Green Human Resource Management (GHRM) is an important research agenda in human resource management practices in modern business companies. This type of research is descriptive qualitative and uses a systematic literature review approach. The purpose study is to provide an overview of the latest research on the application of GHRM, problems that arise in the application of GHRM, policies and operational steps for implementing GHRM, the impact of implementing GHRM, and recommendations for further research studies on the impact of implementing GHRM in the corporate environment. This paper presents a structural overview of 30 peer-reviewed articles published in leading academic journals from 2018 to 2022. This review provides an increased understanding of the current state of research, trends, and future research directions. The literature review framework uses the PRISMA model. Research findings show that the implementation of GHRM is developing in both developed and developing countries, effective GHRM implementation requires organizational commitment and employee participation. The GHRM implementation system is the uniqueness of the organization and the impact of GHRM implementation leads to green managerial innovation and green HR process innovation that supports green management and sustainable green industries.